Cancellous Bone Mechanical Characterization and Finite Element Simulation - Syahrom, Ardiyansyah; Al-Fatihhi bin Mohd Szali Januddi, Mohd.; Harun, Muhamad Noor.; Öchsner, Andreas; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book provides comprehensive mechanobiological insights into bone, including the microstructure of cancellous bone and its realistic loading in the human body. This approach considers different types of loads, i.e. static and dynamic, and the response under uniaxial and multiaxial loading conditions. The book also reviews additional factors influencing biomechanical properties, e.g. fluid transport. In closing, the mechanobiological approach is discussed in the context of the finite element method.
Introduction -- Cancellous Bone -- Monotonic Behavior of Cancellous Bone -- Time-and Cycle-Dependant Behavior of Cancellous Bone -- Transport Phenomena on Cancellous Bone -- Computational Modeling on Cancellous Bone -- Conclusion.
Keywords: Mechanics, Applied; Solids; Biomaterials; Biomedical engineering; Solid Mechanics; Biomaterials; Biomedical Engineering and Bioengineering